Cultural and Linguistic Validation of Foreign Psychometric Instrument -an example of adapting the Suinn-Lew Asian Self-Identity Acculturation (SL-ASIA) Scale, from English to Indonesian Language- - Kwartarini Wahyu Yuniarti (Faculty of Psychology Universitas Gadjah Mada, 2014)
This article is to share best practices of the author in validating foreign research instruments into Indonesian Language. The words of Cultural and Linguistic Validation may not be something new anymore, but the scientific work on the proper cultural and linguistic validation offoreign instruments into Indonesian Lan- guage, in Indonesia, especially psychomet- ric instruments, is probably rarely done.Report of that is very limited, if there is any. Nevertheless, any comments and critics to this article are most welcomed.